Low Prevalence of Salmonella Enterica in Cull Dairy Cattle at Slaughter in Northern Italy - Bonardi, Silvia (Ital J Food Saf, 2017)
In order to evaluate Salmonella carrier status of cull dairy cattle at slaughter, 125 animals were randomly selected during the period February-May 2016. Dairy cows were reared in 89 farms located in two regions of Northern Italy (Lombardy and Emilia-Romagna regions), where bovine milk is primarily used for Parmigiano-Reggiano cheese and Grana Padano cheese production. Samples were collected by swabbing a 400-cm(2) area of the brisket hide and by rectoanal mucosal swabs. They were tested following the reference ISO 6579 method and the isolates were serotyped following the Kauffmann-White-Le Minor scheme and genotyped by XbaI PFGE. Salmonella was detected in 1.6% of the brisket hide samples (2/125) (95% CI: 0.4-5.6) and never found in faecal samples (95% CI: 0-3%). The positive cattle were reared in two farms located only in Emilia-Romagna region. The isolates were typed as S. Derby and S. Seftenberg. The comparison of the pulsed-field gel electrophoresis (PFGE) patterns of the bovine strains with all the PFGE patterns of the same serotypes responsible for human salmonellosis cases notified in Emilia-Romagna region in the years 2013-2015 did not find any correspondence. Therefore, the role of cull dairy cattle in transmitting Salmonella to humans seems to be less important than those of pigs and poultry in EU, but more data are needed for completing attribution source studies.